Coupling dynamics of Nb/Nb2O5 relaxation oscillators. (20th February 2017) - Li, Shuai; Liu, Xinjun; Nandi, Sanjoy Kumar; Venkatachalam, Dinesh Kumar; Elliman, Robert Glen
Abstract: The coupling dynamics of capacitively coupled Nb/Nb2 O5 relaxation oscillators are shown to exhibit rich collective behaviour depending on the negative differential resistance response of the individual devices, the operating voltage and the coupling capacitance. These coupled oscillators are shown to exhibit stable frequency and phase locking states at source voltages as low as 2.2 V, with frequency control in the range from 0.85 to 16.2 MHz and frequency tunability of ∼8 MHz V –1 . The experimental realisation of such compact, scalable and low power coupled-oscillator systems is of particular significance for the development and implementation of large oscillator networks in non-Boolean computing architectures.